PENGARUH INTENSI KEWIRAUSAHAAN, KOMPETENSI INDIVIDU, DAN MODAL USAHA TERHADAP KESUKSESAN USAHA PADA KELOMPOK PENGRAJIN ANYAMAN BAMBU PADUKUHAN MERTELU KULON, GUNUNGKIDUL, YOGYAKARTA - Ita Puspita Hapsari (JUIMA : JURNAL ILMU MANAJEMEN, 2022)
This study aims to determine the effect of entrepreneurial intention, individual competence and venture capital on business success in the Bamboo Weaving Craftsmen Group in Padukuhan Mertelu Kulon, Gunungkidul Regency, Yogyakarta. The research was conducted with a quantitative approach using a questionnaire as a data collection method. The population in this study were all members of the local woven bamboo craftsman group, amounting to 75 people. The sampling technique uses a saturated sample, which means that the entire population is used as a sample. The location of this research is Mertelu Kulon Hamlet, Mertelu Village, Gedangsari District, Gunungkidul Regency, DI Yogyakarta Province. Then for data analysis using multiple linear regression techniques which are then processed with the SPSS 16 application. The results of this study conclude that entrepreneurial intentions do not have a positive and significant effect on business success, individual competencies have a positive and significant effect on business success, business capital has a positive and significant effect on business success, and entrepreneurial intentions, individual competencies, and business capital have a significant effect on business success. simultaneously to business success.